Design and Wheel Torque Performance Test of the Electric Racing Car Concept E-Falco - Hadi Pranoto; Bambang Darmonoa; Zainal Arifin; Ibnu Susanto (Institute for Research on Innovation and Industrial System (IRIS), 2021)
To reduce the use of fossil fuels in vehicles and reduce exhaust emissions, it is necessary to use electric vehicle technology. Solidworks software is used in designing and manufacturing an electric car and a simulation is carried out using CFD (Computation Fluid Dynamic) software to determine the strength of the frame structure and air drag when the electric car is running. The performance test of the motor by using the dyno test to determine the acceleration time, power, and torque of the motor. The results of the simulation show that at a speed of 10 km/h the air drag is 6.24 N, a speed of 20 km/h is 24.64 N, and a speed of 40 km/h is 93.92 N. The results of the dyno test shows that the acceleration time with full acceleration from a speed of 0-70 km/h is 13.63 seconds, the maximum power output by the motor is 14.17 hp occurs at a speed of 36-53 km/h and the amount of peak torque released by the motor occurs at a speed of 13 km/h at 228 Nm.